2015
DOI: 10.1002/mnfr.201400592
|View full text |Cite
|
Sign up to set email alerts
|

Rooibos flavonoids, orientin and luteolin, stimulate mineralization in human osteoblasts through the Wnt pathway

Abstract: Orientin and luteolin, flavonoids in rooibos tea, enhance mineral content in Saos2 cells. These findings provide guidance for doses to be studied in well-established animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 62 publications
2
47
0
Order By: Relevance
“…Our data demonstrated that osteoblastic cells treatment with apigenin and luteolin at a concentration of 1  μ M significantly increased the transcriptional level of COL-I, OPN, and OCN (Figure 9(a)). Similar concentrations of these two compounds have been used, and our findings are in agreement with the other experiments [2628]. In a previous study, we reported that linarin extracted from FCI enhanced the osteoblast differentiation in MC3T3-E1 cells in a dose-dependent manner [11].…”
Section: Resultssupporting
confidence: 92%
“…Our data demonstrated that osteoblastic cells treatment with apigenin and luteolin at a concentration of 1  μ M significantly increased the transcriptional level of COL-I, OPN, and OCN (Figure 9(a)). Similar concentrations of these two compounds have been used, and our findings are in agreement with the other experiments [2628]. In a previous study, we reported that linarin extracted from FCI enhanced the osteoblast differentiation in MC3T3-E1 cells in a dose-dependent manner [11].…”
Section: Resultssupporting
confidence: 92%
“…Flavonoids are a large class of phyto-chemicals that are widely distributed in plant foods [1417]. Flavonoids have been found to decrease urinary excretion of calcium and phosphate, increase osteoblast activity, decrease osteoclast activity, and protect against the loss of trabecular thickness [1820]. Previous studies showed that different plant-derived flavonoid compounds can stimulate osteoblasts function, and inhibit osteoclasts functions either alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…First, in vitro co-culture studies with plasma cells and osteoblasts are limited by the lack of relevant osteoblast cell lines. The human bone marrow stroma cell lines HS-5 and HS-27 do not differentiate into osteoblasts, and other cell lines that do mineralize, such as Saos2 [41] and MG-63 [42], are actually osteosarcoma rather than osteoblast cell lines. Certain cell lines, such as the human fetal osteoblastic cell line hFOB1.19[43], which proliferate at 33.4°C and differentiate at 39.4°C or in osteogenic medium, have been explored in multiple myeloma in vitro cultures [44] and could be exploited further.…”
Section: Effects Of Osteoblasts On Multiple Myelomamentioning
confidence: 99%